2012
DOI: 10.1258/ijsa.2012.012017
|View full text |Cite
|
Sign up to set email alerts
|

Depression and dietary intake in a cohort of HIV-positive clients in Sydney

Abstract: This cross-sectional study aimed to compare dietary intake in people living with HIV (PLHIV) experiencing symptoms of depression with those not reporting depression. The Centre for Epidemiologic Studies Depression Scale (CES-D10) was used to classify the risk of depression. Dietary nutrient intake was determined using the diet history and food frequency questionnaire. Depressed (n = 21) compared with non-depressed (n = 37) subjects had significantly lower mean intake of fibre (16.1 versus 25.4 g/day), vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These studies were published between 2009 and 2022. 12 of the included studies were performed in Asian countries [Korea ( 21 , 26 , 28 , 34 , 35 , 41 ), Iran ( 25 , 37 , 39 ) and Japan ( 19 , 20 , 31 )], and the other ones were conducted in United States ( 22 , 24 , 33 , 40 , 43 ), Brazil ( 32 , 38 , 42 ), Australia ( 23 , 36 ), Spain ( 29 , 30 ), and Turkey ( 27 ). Male, female and both male and female participants were recruited in 2 ( 25 , 36 ), 8 ( 21 , 26 , 32 , 34 , 37 39 , 43 ), and 15 ( 19 , 20 , 22 24 , 27 31 , 33 , 35 , 40 42 ) studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were published between 2009 and 2022. 12 of the included studies were performed in Asian countries [Korea ( 21 , 26 , 28 , 34 , 35 , 41 ), Iran ( 25 , 37 , 39 ) and Japan ( 19 , 20 , 31 )], and the other ones were conducted in United States ( 22 , 24 , 33 , 40 , 43 ), Brazil ( 32 , 38 , 42 ), Australia ( 23 , 36 ), Spain ( 29 , 30 ), and Turkey ( 27 ). Male, female and both male and female participants were recruited in 2 ( 25 , 36 ), 8 ( 21 , 26 , 32 , 34 , 37 39 , 43 ), and 15 ( 19 , 20 , 22 24 , 27 31 , 33 , 35 , 40 42 ) studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 41 to 25895 for a total number of 91966. The dietary vitamin C and E intake was assessed by food-frequency questionnaire (FFQ) in 14 studies ( 19 , 20 , 22 , 23 , 25 , 26 , 28 , 30 , 31 , 36 , 37 , 39 , 42 , 43 ), and recall method in 12 studies ( 21 , 24 , 25 , 27 , 29 , 32 35 , 38 , 40 , 41 ). The diagnostic criteria of depression or depressive symptom were Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) ( 27 , 30 ), Patient Health Questionnaire-9 (PHQ-9) ( 24 , 33 , 35 , 40 ), Center for Epidemiological Studies Depression Scale (CES-D) ( 19 – 21 , 23 , 29 , 34 , 38 , 43 ), Beck Depression Inventory (BDI) ( 25 27 , 32 , 39 ), Geriatric Depression Scale (GDS) ( 31 , 36 ), Depression, Anxiety, Stress Scale (DASS) ( 37 ), National Institute of Mental Health (NIMH) ( 22 ), and Clinical Interview Schedule Revised (CIS-R) ( 42 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2009 and 2022. 14 of the included studies were performed in Asian countries [Korea ( 14 , 20 , 21 , 25 , 29 , 30 , 35 , 36 ), Iran ( 18 , 31 , 33 ), Japan ( 13 , 23 ) and China ( 28 )], and the other ones were conducted in United States ( 15 , 17 , 27 , 32 , 34 ), Brazil ( 26 , 37 ), Australia ( 16 ), Spain ( 22 , 24 ), and Turkey ( 19 ). Male, female and both male and female participants were recruited in 1 ( 18 ), 8 ( 14 , 20 , 26 , 28 , 30 , 31 , 33 , 36 ), and 16 ( 13 , 15 17 , 19 , 21 25 , 27 , 29 , 32 , 34 , 35 , 37 ) studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 41 to 17,401 for a total number of 100,955. The exposure was assessed by food-frequency questionnaire (FFQ) in 16 studies ( 13 – 16 , 18 , 20 , 21 , 23 25 , 28 , 29 , 31 , 33 , 36 , 37 ), and recall method in 9 studies ( 17 , 19 , 22 , 26 , 27 , 30 , 32 , 34 , 35 ). The diagnostic criteria of depression were Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) ( 15 , 17 , 19 , 24 ), Patient Health Questionnaire-9 (PHQ-9) ( 27 , 29 , 32 , 34 ), Center for Epidemiological Studies Depression Scale (CES-D) ( 13 , 14 , 16 , 22 , 28 , 30 ), Beck Depression Inventory (BDI) ( 18 , 20 , 21 , 26 , 33 , 36 ), Geriatric Depression Scale (GDS) ( 23 ), Clinical Interview Schedule Revised (CIS-R) ( 37 ), and Depression, Anxiety, Stress Scale (DASS) ( 31 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Using the Center for Epidemiologic Studies Depression Scale to classify the risk of depression, Purnomo et al [90] reported that depressed subjects had a significantly lower mean intake of fiber, vitamin A, magnesium, and folate compared with nondepressed subjects. Using the Center for Epidemiologic Studies Depression Scale to classify the risk of depression, Purnomo et al [90] reported that depressed subjects had a significantly lower mean intake of fiber, vitamin A, magnesium, and folate compared with nondepressed subjects.…”
Section: Exercise and Behavioral Lifestyle Changesmentioning
confidence: 99%